KAUSALITAS INFRASTRUKTUR TRANSPORTASI, FOREIGN DIRECT INVESTMENT (FDI) DAN PERTUMBUHAN EKONOMI DI INDONESIA - Hana Raghdsifa A W; Hasdi Aimon; Mike Triani (Jurnal Ecogen, 2018)
The aims of this study are to analyze the causal relationship between transportation infrastructure, foreign direct investment (FDI) and economic growth in Indonesia. The type of research used was descriptive associative. This study used secondary data and using time series data from 1987-2017 which were analyzed using Vector Auto Regression (VAR) analysis and continued with VECM analysis. The results of the VAR analysis have indicated that there is a causal relationship between the variables of transportation infrastructure and foreign direct investment (FDI), there is a one-way relationship between the variables of transportation infrastructure affecting economic growth and there is a one-way relationship between economic growth variables affecting foreign direct investment (FDI).  Keywords: Transportation Infrastructure, foreign direct investment (FDI), economic growth (GDP)